Engaging every learner: Differentiated educational materials for renewable energy - Regina Bilqis Wardani; Nurul Fitriyah Sulaeman; Zeni Haryanto (Universitas Muhammadiyah Malang, 2024)
The learning approach in the classroom is often centered on the role of the teacher, so the development of teaching materials based on differentiated learning is important to meet diverse learning needs. Therefore, this study aims to describe the validity and student responses to teaching materials based on differentiated learning on renewable energy materials. The research method used is Research and Development (R&D) with the ADDIE model. Data collection was done through observation, questionnaires, and interviews. Data analysis techniques include learning style analysis, feasibility and validity of teaching materials, and student responses to questionnaires. The subjects of this study were 35 students of class X-11 of State High School in Samarinda City and the object of research was teaching materials based on differentiated learning on renewable energy material. The results showed that the teaching materials were in the highly valid category, with a percentage score of 88% in the material aspect and 89% in the media aspect. The results of student responses showed a percentage score of 81%. Trials on a wider sample need to be carried out to ensure the effectiveness of this approach if students have the same circumstances, especially learning styles.